Makna Pengendalian Keuangan Tanpa SAK ETAP Pada Usaha Jasa Photocopy Area Gresik Kota Baru - Hariyati, Rizka Octavia; Santoso, Rahmat Agus (Jurnal Mahasiswa Manajemen, 2022)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the economy of a region, especially in Indonesia. Photocopy service businesses that carry out financial records using simple bookkeeping without using SAK ETAP and financial control systems, but their business continues to increase as seen from the remaining balance. This study aims to analyze the meaning of financial control without using SAK ETAP in photocopying service businesses in Gresik Kota Baru. The research approach is descriptive qualitative. Data collection techniques using the method of documentation and interviews with the selection of informants using purposive sampling technique. The data analysis technique uses an interactive model. The results of this study indicate that the meaning of financial control according to the photocopy service business owner is to spend income or income received and meet consumer needs, and regulate expenditure so that it is not more than the income received. In carrying out financial control, there are how to control activities, constraints, and impacts if you do not carry out financial control. This research can provide information as input for business owners in policy making in order to improve performance in presenting financial statements in accordance with financial accounting standards and using management control systems, especially financial control. This study only examines the meaning of financial control from aspects of financial accounting standards and from financial reports so that the results obtained are less broad.